Analyze the customer satisfaction and management perception of Grameenphone; gap analysis in between the customer expectation and the management perception - Ahmed, Shabbir (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.